C-N-S synergy in a pilot-scale mainstream anammox fluidized-bed membrane bioreactor for treating chemically enhanced primary treatment saline sewage. (1st February 2023) - Huang, Xiaowu; Mi, Wenkui; Chan, Yuen Him; Singh, Shubham; Zhuang, Huichuan; Leu, Shao-Yuan; Li, Xiang-zhong; Li, Xiangdong; Lee, Po-Heng
Highlights: Mainstream anammox is successfully applied to treat CEPT saline sewage in pilot-scale. Startup of pilot-scale mainstream anammox from activated sludge is feasible. Kuenenia responds to N removal in the saline mainstream anammox process. Synergetic AMX, SRB, SOB, and DNB accomplish the removal of C-N from saline sewage. NOB washout is not obligatory to succeed mainstream anammox, but NOB suppression does. Abstract: Seawater for toilet flushing conserves the scarce freshwater resources in Hong Kong and similar densely-populated coastal cities. Saline sewage treatment using energy-efficient anammox-based processes appears to be beneficial, with notable potential for the future. However, the feasibility of this process remains uncharted, especially from its start-up to its steady-state cooperation. In this study, a pilot-scale mainstream anammox process was succeeded in a granular activated carbon fluidized-bed membrane bioreactor (FMBR) with only inoculating saline anaerobic digestion sludge. The FMBR, operating at the dissolved oxygen (DO) of 0.04-0.16 mg/L, achieved comparable nitrogen removal rates of 50.1-78.3 g N/m 3 /d while treating real chemically enhanced primary treatment saline sewage at 3.2 m 3 /d. Excluding Scalindua, 16S rRNA gene amplicon sequencing revealed a high abundance of common-freshwater-observed Kuenenia from 0.2% (day 259) to 1.3% (day 332) in biofilms. Nitrosomonas, responsible for ammonium oxidation, dominated in biofilms and accounted for 1.8%-9.2%. Nitrite oxidizing bacteria incursion happened unexpectedly, due to high oxygen exposure/supply from temporary on-site technical difficulties; however, NOB suppression was achieved by controlling DO at <0.16 mg/L, leading the FMBR's stability over the 343-day operation. Sulfate-reducing bacteria and sulfur-dependent denitrifiers propagated with high abundance, representing 14.0±10.6% and 6.0±2.0% in suspensions and 7.2±1.8% and 15.9±2.3% in biofilms, respectively. Further, metagenomic sequencing analysis indicated the C-N-S synergy of nitritation, anammox, sulfate reduction, and mixotrophic denitrification in the FMBR. Importantly, this research found that such a novel C-N-S synergy was made by the scavenges of hydrogen sulfide by Gammaproteobacteria sp. (B01 and B19) and Thioalkalispiraceae sp. (B03 and B04), species having ascendancy subsisting in the presence of oxygen owing to their aptitude of detoxifying reactive oxygen species. Knowledge gleaned from this study, as well as a complete set of pilot experimental data, could serve as a strong technical base for the larger-scale application of this process. Graphical Abstract: Image, graphical abstract